A First Clinical Trial on Botulinum Toxin-A for Chronic Muscle-Related Pain in Cerebral Palsy - Jacobson, Dan; Löwing, Kristina; Kullander, Kjell; Rydh, Britt-Marie; Tedroff, Kristina (Frontiers in Neurology, 2021)
Objective: To test if Botulinum toxin-A (BoNT-A) is effective in reducing chronic muscle-related pain in adults with spastic cerebral palsy (CP), as compared to placebo. Design: A single-center, double-blind, parallel, randomized placebo-controlled trial. The design included an interim analysis to allow for confirmatory analysis, as well as, pilot study outcomes. Setting: Tertiary university hospital. Participants: Adults with spastic CP and chronic pain associated with spastic muscle(s). Intervention: Treatment was one session of electromyographically (EMG) guided intramuscular injections of either BoNT-A or placebo normosaline. Main study outcomes: The primary outcome was the proportion who achieved a reduction of pain intensity of ≥2 steps on the Numerical Rating Scale (NRS) six weeks after treatment. Results: Fifty individuals were screened for eligibility, whereof sixteen were included (ten female, six male, mean age 32 years SD 13.3 years). The randomization yielded eight participants per treatment arm, and all completed the study as randomized. The study was stopped at the interim analysis due to a low probability, under a preset threshold, of a positive primary outcome. Four individuals were treatment responders in the BoNT-A group for the primary outcome compared to five responders in the placebo group (p=1.000). Adverse events were mild to moderate. In exploratory analysis, the BoNT-A group had a trend of continuing reduction of pain at the last follow-up, after the primary endpoint. Conclusions: This study did not find evidence that BoNT-A was superior to placebo at the desired effect size (Numbers Needed to Treat of 2.5) at six weeks after treatment.